2007
DOI: 10.3200/socp.147.5.477-500
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Antecedents and Consequences of Psychological Ownership in Organizational Settings

Abstract: Psychological ownership is a feeling of possession in the absence of any formal or legal claims of ownership. The aim of our research was to extend previous empirical testing psychological ownership in work settings to encompass both job-based and organization-based psychological ownership, related work attitudes and behavioral outcomes.Questionnaire data from 68 employees and their managers revealed both job-based and organization-based psychological ownership as distinct work attitudes, distinguishable from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
225
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(254 citation statements)
references
References 56 publications
9
225
2
3
Order By: Relevance
“…Van Dyne and Pierce (2004) found that psychological ownership was associated with increased organizational commitment, job satisfaction, organization-based self-esteem, and organizational citizenship. As noted above, Mayhew et al (2007) revealed that organization-based psychological ownership has a positive relationship with affective organizational commitment and job satisfaction. Avey et al (2009) showed that psychological ownership was positively related to transformational leadership, organizational citizenship, affective commitment, job satisfaction, and intention to stay, and negatively related to workplace deviance.…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 95%
See 4 more Smart Citations
“…Van Dyne and Pierce (2004) found that psychological ownership was associated with increased organizational commitment, job satisfaction, organization-based self-esteem, and organizational citizenship. As noted above, Mayhew et al (2007) revealed that organization-based psychological ownership has a positive relationship with affective organizational commitment and job satisfaction. Avey et al (2009) showed that psychological ownership was positively related to transformational leadership, organizational citizenship, affective commitment, job satisfaction, and intention to stay, and negatively related to workplace deviance.…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 95%
“…Mayhew et al (2007) similarly defined psychological ownership as a feeling of possession without any formal or legal assertion of ownership. Van Dyne and Pierce (2004) defined psychophysical ownership as the psychological phenomenon of developing employee-specific feelings about both tangible and intangible objects (e.g., a group, job, work tools, organization).…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
See 3 more Smart Citations